STATUS HARA TANAH DAN PERTUMBUHAN PEPAYA CALIFORNIA (Carica papaya L.) TERHADAP MOL NASI BASI: SOIL NUTRITION STATUS AND GROWTH OF CALIFORNIA PAPAYA (Carica papaya L.) TO SPOILED RICE MOL - Siti Mutmainah; Ahmad Sufillah Zaini (Universitas Widya Gama Mahakam, 2021)
Papaya is a tropical fruit that is easy to cultivate and is one of the fruits that is widely consumed by people in Indonesia. Papaya California is one of the papaya varieties that are favored by the public because it has a sweeter taste than other papaya varieties. In an effort to reduce the use of inorganic fertilizers, the researchers made MOL made from spoiled rice in the hope that it can be used as an alternative in the cultivation of Californian papaya. This study used a randomized block design, where the researchers wanted to see how the MOL response of stale rice to soil nutrient status and growth of California papaya plants. The MOL of spoiled rice consisted of 4 levels, namely: N0 = 0 ml/L (control), N1 = 50 ml/L, N2 = 100 ml/L and N3 = 150 ml/L. The data obtained were analyzed and further tested with the 5% BNT test. The results showed that giving MOL of stale rice with this concentration had no significant effect on all observation parameters and was not significant in improving soil nutrient status.